Playing with ionic liquids to uncover novel solid polymer electrolytes - Leones, Rita Daniela Barros (2017)
Solid polymer electrolytes (SPEs) based on chitosan and fourteen ionic liquids (ILs) were synthesized by solvent casting method. All ILs had in common a 1-ethyl-3-methylimidazolium cation ([C2mim]+). Therefore, this study focuses on the influence of the anion on the thermal, morphological, and electrochemical properties of the SPEs. The samples were analyzed by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), complex impedance spectroscopy (ionic conductivity) and cyclic voltammetry. The SPEs displayed an amorphous morphology, a thermal stability higher than the one obtained for the pure chitosan matrix (>140 ºC), a maximum room temperature (T = 25 ºC) ionic conductivity of 1.61 x 10-3 S cm-1 and a wide electrochemical window of ~ 4.0 V.